Tourism industry as a competitive advantage of Greece during and after the economic crisis: Financial analysis of selected hotel and shipping companies - Pazarskis Michail; Kourtesi Sofia; Konstantinidis Christos; Mavridis Mavroudis (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
The tourism industry is very important to the economic prosperity of a country, even in a period of economic crisis. In last decade, tourism industry of Greece, which contributes significantly to the country's economy, faced many problems challenges during the economic crisis. To shed light on this situation, Greek-listed companies in the tourism industry were examined in recent years (during and after the economic crisis) and we tried to draw safe conclusions about their financial performance. Our sample consisted of all Greek listed companies in the tourism industry, i.e., four hotels and four shipping companies, while several univariate statistical tests (t-test, Kruskal-Wallis tests) have been applied to their accounting data (financial ratios) for comparison between them, during and post crisis period. The study results underlined that the financial position of all the sample companies was deteriorated during the crisis. This study could be useful for extracting knowledge from the current state of the Greek tourism industry to potential investors, managers, the Greek Ministry of Tourism and Finance or other government authorities, tax policy and related issues in tourism business activities, and the banking system.
Keywords: L83; M41; Z30; 330; Hotel; tourism; financial variables; Greece; economic crisis